(untitled) (Al-Aasar, 2026)
This study explores the concept of Wujūdiyat (Existentialism) with special reference to the novels Aag ka Darya by Qurratulain Hyder and Karwan-e-Wujood. Existentialism, as a philosophical movement, foregrounds individual freedom, anxiety, alienation, identity crisis, and the search for meaning in a seemingly absurd world. This research investigates how these existential concerns are artistically represented within the socio-historical and cultural contexts of the selected texts.In Aag ka Darya, the continuity of history and the fragmentation of identity reflect the existential dilemma of man caught between tradition and modernity. The characters struggle with displacement, loss of belonging, and the quest for self-realization across different epochs. Similarly, Karwan-e-Wujood presents the inner turmoil of individuals confronting moral uncertainty, spiritual emptiness, and the burden of choice in a rapidly changing society. By employing a qualitative and analytical methodology, this study examines thematic structures, characterization, and narrative techniques to highlight the existential dimensions embedded in these works. The research concludes that both novels not only embody existential philosophy in a localized South Asian context but also reinterpret it through indigenous cultural, historical, and metaphysical perspectives. Thus, Wujūdiyat in Urdu fiction emerges as a dynamic synthesis of Western existential thought and Eastern intellectual traditions.